Emotion Analysis of E-Customers Using Face Recognition - Navle, Sagar; Athawale, Uttara (International Journal of Computer Sciences and Engineering, 2019)
In Today’s world it is easy to recognize the emotion of a person by just looking at his/her facial expressions. For a sales person it is important to know whether his customers is convinced to buy a product or not, the factors through which he can identify this is by observing the behaviour and emotions. For e-commerce such as Amazon and Flipkart it becomes difficult to identify the emotional state of a person. The interaction and communication between human beings and computers will be more natural if computers are able to understand and respond to the emotions of an individual [1]. This paper provides us a way through which the e-commerce business can plan strategies, recommend relevant products and keep a track of customer’s habit using facial emotions.